Habitual daily steps outperform body mass index in predicting VO₂max among recreationally active young adults - Nanda Rimawati; Roy Januardi Irawan; Himawan Wismanadi; Heri Wahyudi; Afif Rusdiawan (Sriwijaya Journal of Sport, 2026)
Research Background: Cardiorespiratory fitness, commonly assessed through maximal oxygen uptake (VO₂max), is a key indicator of overall health and physical performance. Physical activity and body composition are considered important determinants of VO₂max; however, findings remain inconsistent, particularly among young, recreationally active populations. Research Objectives: This study aimed to examine the associations between physical activity (measured by daily step count) and body mass index (BMI) and VO₂max among recreationally active university students. Method: A cross-sectional study was conducted involving 53 male university students aged 18–21 years. Physical activity was assessed using daily step count recorded over five consecutive days, while VO₂max was estimated using the Multistage Fitness Test (MFT). BMI was calculated from measured body weight and height. Data normality was assessed using the Shapiro–Wilk test, and associations between variables were analyzed using Spearman’s rank correlation. Results: A strong, statistically significant positive correlation was observed between mean daily step count and VO₂max (r = 0.831, p < 0.001). In contrast, no significant correlations were observed between BMI and step count (r = -0.063, p = 0.656) or between BMI and VO₂max (r = -0.064, p = 0.650). Conclusion: These findings indicate that habitual physical activity, as reflected by daily step count, is strongly associated with cardiorespiratory fitness, whereas BMI does not appear to be a significant determinant in this population. Promoting consistent daily movement may be an effective strategy to enhance aerobic fitness among young adults.